The child Musicality Index: A child-friendly version of the Goldsmiths Musical Sophistication Index - Chloe MacGregor; Solena Mednicoff; David J. Vollweiler; Erin Hannon; Daniel Müllensiefen (PLoS ONE, 2026)
The Goldsmiths Musical Sophistication Index (Gold-MSI) has contributed significantly to the study of musical sophistication in adolescence and adulthood, however the field lacks an equivalent self-report instrument for childhood. Existing measures focus heavily on instrumental learning and fail to consider social, emotional and motivational factors which are likely to underlie engagement with music. To address this gap, the current research introduces the child Musicality Index (cMI), a new psychometric self-report measure of musicality for 6- to 13-year-olds which captures children’s motivation for and enjoyment of music. In study 1, a large cohort (N = 302) of children (6–13yrs) responded to items adapted from the Gold-MSI to suit a younger age range. Factor analysis (N = 283) was used to select 8 items for the children’s version of the measure, split into two group factors (‘musical drive’ and ‘enjoyment of music making’) and one general factor (‘musicality’). Studies 1b and 1c then investigated whether children’s responses to these 8 items were valid and reliable (N = 250–460). Study 2 provided evidence for the psychometric properties of the final 8-item version of the task in a new sample (N = 56). The new, 8-item cMI provides a short and robust measure which can facilitate investigation of the most critical aspects of musicality during childhood. It has demonstrated good psychometric properties in UK and US samples and is now openly available for use in wider research.